If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(2x + 3) + -3x(-4 + -2x) = 0 Reorder the terms: 5x(3 + 2x) + -3x(-4 + -2x) = 0 (3 * 5x + 2x * 5x) + -3x(-4 + -2x) = 0 (15x + 10x2) + -3x(-4 + -2x) = 0 15x + 10x2 + (-4 * -3x + -2x * -3x) = 0 15x + 10x2 + (12x + 6x2) = 0 Reorder the terms: 15x + 12x + 10x2 + 6x2 = 0 Combine like terms: 15x + 12x = 27x 27x + 10x2 + 6x2 = 0 Combine like terms: 10x2 + 6x2 = 16x2 27x + 16x2 = 0 Solving 27x + 16x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(27 + 16x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(27 + 16x)' equal to zero and attempt to solve: Simplifying 27 + 16x = 0 Solving 27 + 16x = 0 Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 16x = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 16x = 0 + -27 16x = 0 + -27 Combine like terms: 0 + -27 = -27 16x = -27 Divide each side by '16'. x = -1.6875 Simplifying x = -1.6875Solution
x = {0, -1.6875}
| 2x+60+4x= | | a+(4+a)=18 | | 2/4y=16 | | -8+x=14 | | 21=2(4z-5) | | 4a-2a=-12-2a | | -2x^2+2px-3=0 | | 4x(3x-2)-x(-3x-2)= | | -2(x-4)=7x-19 | | 0=1y+3x+1 | | 6y-11=30whatisy | | 4z/7-8=1 | | 9m-1=10m+8 | | 9n=5n+8 | | (k-2)*x^2-2kx+3k-1=0 | | -3+-3b+1=6b-8 | | 7x(3/4*x-2)=0 | | -7d=-5d-10 | | 2x+12=-15 | | 5k+10=-9+7k+1 | | 4x(x+4.5)=90 | | 3(3x+4x)=66 | | w-1=-10-2w | | x/9-4=0 | | r-7=5r+9 | | -3u=8-4u | | 7d+3=17 | | 2s-7=9-6s | | 5x(3x+2)+3x(4x-5)= | | 3y-y=0 | | -g+9=8g | | 6y=7y+9 |